THE PAINTING TECHNIQUE ON THE COMBINATION OF TRADITIONAL ORNAMENTAL COLLAGE AND SPLATTERING - Deni Junaedi (ARTISTIC : International Journal of Creation and Innovation, 2026)
Creativity is vital in the world of painting. It can be created in relation to forms and techniques. In terms of form, this study adapted traditional Indonesian ornaments to a contemporary taste. The use of antique ornaments in the present context illustrates the postmodern art principle, specifically “shock of the old,” not “shock of the new”. At the technical level, this study integrates collage with splattering. The novelty of collage techniques lies in the independent creation of traditional Nusantara ornament forms through digital printing on canvas rather than with current print media. The application of the splattering technique responds to the collage, thereby blending artistically. The resulting artwork illustrates that the interplay between traditional visual elements and expressive splattering techniques can yield a harmonious aesthetic. This research produces novel aesthetic opportunities in contemporary painting.